Structure Strength Analysis for the Box of One Power Take-off - Zhang Wenbo; He Lin; Jiang Hongwan (Jixie chuandong)
Taking the box of power take-off as the main research object,the box,gear,axis and other three-dimensional entity model are created by using the CAD software UG,and the models are inputted into ANSYS Workbench through the data exchange interface and respectively taken statics analysis and dynamics analysis of the box to obtain the box stress distribution.Then,it provides theoretical basis for accurate structure strength analysis and reliable optimizing design of the box through comparing different analysis results.